Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

how to solve through elimination the following 2m=-4n-4 and 3m+5n=-3


Sagot :

naǫ
[tex]2m=-4n-4 \ \ \ |\times (-3) \\ 3m+5n=-3 \ \ \ |\times 2 \\ \\ -6m=12n+12 \\ \underline{6m+10n=-6} \ \ \ |\hbox{add the sides of the equations} \\ 10n=12n+12-6 \\ 10n=12n+6 \ \ \ |-12n \\ -2n=6 \ \ \ |\div (-2) \\ n=-3 \\ \\ 2m=-4n-4 \\ 2m=-4 \times (-3)-4 \\ 2m=12-4 \\ 2m=8 \ \ \ |\div 2 \\ m=4 \\ \\ (m,n)=(4,-3)[/tex]